Genesis and spatial distribution of upland soils in east central Kansas - Presley, DeAnn R. (Kansas State University, 2007)
Upland soils in east central Kansas have a complex genesis, often contain one or more paleosols, and form in multiple parent materials including loess, colluvium, residuum, and alluvium. Quaternary loess/paleosol investigations have largely ignored this region of Kansas, as the total loess thickness on uplands is <2 m thick. In this study, the objectives are to examine the morphology and genesis of the soils of interest and how these characteristics vary within soil profiles, across landscapes, and throughout the current series mapping extent. The series of interest include the Irwin, Konza, Dwight, and Ladysmith soil series. Methods used in this study include field descriptions and sampling, terrain analysis, micromorphological investigations, and laboratory characterization, including silt and clay mineralogy. Accelerator mass spectrometry (AMS) was used for numerical dating and determination of stable carbon isotope values (δ13C) for selected paleosols. Radiocarbon ages ranged from 24,000 to 19,000 yr BP and δ13C values were between -19 and -17 ‰ (PDB), indicating that the paleosols were formed in Gilman Canyon loess or the Severance formation, under a mix of C3 and C4 vegetation. Terrain analysis results illustrated that, in given drainage areas, the soil series were mapped on a wide range of slope positions. Field observations and terrain analysis confirmed no relationships between mollic epipedon thickness, solum thickness, paleosol thickness, or depth to the paleosol with respect to landform. Micromorphological investigations revealed increasing soil development with depth, i.e., the presence of two paleosols beneath the modern soil. Mean particle size and mineralogy vary geographically within individual series. Pedogenic carbonate accumulations and redoximorphic concentrations are common features of the soils of interest, and less common features include sodium and gypsum accumulations, slickensides, and redoximorphic depletions. Results from this study will be provided to the USDA-NRCS for use in future soil survey updates, and will contribute to Quaternary loess/paleosol knowledge in Kansas and the Great Plains.
Keywords: loess; paleosols; genesis; soil; kansas; mapping; Agriculture, Agronomy (0285)